2017
DOI: 10.1371/journal.pone.0173503
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of the therapeutic effect of magnolol on MPTP-induced mouse model of Parkinson’s disease using in vivo 18F-9-fluoropropyl-(+)-dihydrotetrabenazine PET imaging

Abstract: 18F-9-Fluoropropyl-(+)-dihydrotetrabenazine [18F-FP-(+)-DTBZ] positron emission tomography (PET) has been shown to detect dopaminergic neuron loss associated with Parkinson’s disease (PD) in human and neurotoxin-induced animal models. A polyphenol compound, magnolol, was recently proposed as having a potentially restorative effect in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)- or 6-hydroxydopamine-treated animal models. In this study, 18F-FP-(+)-DTBZ PET was used to determine the therapeutic efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…All PET images were processed and analyzed by using the PMOD image analysis software (v3.5, PMOD Technologies Ltd., Zurich, Switzerland). To lower the possible bias from manual VOIs (volume of interests) drawing, an early phase PET template was created with the first 10 min mean PET image acquisition from each animal based on the rigid matching function of to the PMOD built-in mouse T2 MRI template (the procedure for the PET image template creation is shown in Figure S2) [40,41]. Then all other PET images were spatially normalized to this early phase PET template and the different VOIs, including the hippocampus, striatum, cortex, midbrain, and cerebellum from the MRI template were applied for image quantitation (the representative VOI selection image is shown in Figure 7).…”
Section: In Vivo Animal Pet Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…All PET images were processed and analyzed by using the PMOD image analysis software (v3.5, PMOD Technologies Ltd., Zurich, Switzerland). To lower the possible bias from manual VOIs (volume of interests) drawing, an early phase PET template was created with the first 10 min mean PET image acquisition from each animal based on the rigid matching function of to the PMOD built-in mouse T2 MRI template (the procedure for the PET image template creation is shown in Figure S2) [40,41]. Then all other PET images were spatially normalized to this early phase PET template and the different VOIs, including the hippocampus, striatum, cortex, midbrain, and cerebellum from the MRI template were applied for image quantitation (the representative VOI selection image is shown in Figure 7).…”
Section: In Vivo Animal Pet Studiesmentioning
confidence: 99%
“…To further evaluate the tracer deposition in the transgenic mouse animal model, the 6-mo-old animals were sacrificed immediately after in vivo PET imaging procedure and applied for the ex vivo autoradiography as in our previous work [41]. Briefly, the animal was sacrificed with cervical dislocation and then the brain was quickly removed and frozen in dry ice.…”
Section: Ex Vivo Autoradiographymentioning
confidence: 99%
“…Dopaminergic neurons degeneration is one of the main pathological characteristics of Parkinson's disease (PD). Magnolol has been shown the neuroprotective activity to reverse the damage induced by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) using 18 F-FP-(+)-DTBZ animal positron emission tomography (PET) [13]. Cholinergic deficits and neuronal dysfunction contribute to Alzheimer's disease (AD).…”
Section: Neuroprotective Activitymentioning
confidence: 99%
“…Both magnolol and honokiol are isolated from the stem bark of a traditional Chinese herbal medicine Magnolia officinalis , which has been used for management of nervous disturbance, abdominal distention or disorders, gastrointestinal food stagnancy, and coughing and dyspnea [1]. Magnolol has showed a wide spectrum of beneficial activities, including anti-inflammation [2, 3], antimicroorganism [4, 5], antioxidation [6, 7], antiangiogenesis [8, 9], anticancer [1012], neuroprotection [13, 14], cardiovascular protection [15, 16], and lipolysis activities [17, 18]. However, there are still some differences between magnolol and honokiol in safety and toxicology, which have been reviewed by Sarrica et al (2018)[19].…”
Section: Introductionmentioning
confidence: 99%
“…A group of investigators claimed that schisantherin A (a dibenzocyclooctadiene lignan) from Schisandra chinensis fruit protects against 6-hydroxydopamine (6-OHDA) (a PD model) induced dopaminergic neuronal damage in Zebrafish and cytotoxicity in SHSY5Y cells by regulating intracellular ROS accumulation and inhibiting NO production [128]. Weng et al, showed that 6 days daily intraperitonial injection of 10 mg/kg magnolol reversed the neuronal damage associated with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) induced dopaminergic neurotoxicity (the toxin which produces symptoms like PD) in male C57BL/6 mice [129].…”
Section: Lignans With Anti-pd Effectmentioning
confidence: 99%